Comparison of a Seven Conventional Phenotypic Methods with Polymerase Chain Reaction for Detection of Methicillin-Resistant Staphylococcus aureus - M. Al-Mohana, Ali; N. Hussein, Azhar; K. Al-Kudheiri, Mee’aad (Al-Qadisiyah Journal of Pure Science, 2018)
Early detection of methicillin-resistant Staphylococcus aureus (MRSA) is critical for both the management of infected patients, and the timely institution of appropriate infection control measures. Although detection of the mecA gene by polymerase chain reaction (PCR) remains the gold standard, this technology is inaccessible for many laboratories. Therefore, this study sought to evaluate seven phenotypic methods and compare them with PCR. A total of 135 S. aureus were collected from 343 clinical samples between August 2012 and January 2013 from several clinical sources that were randomly selected from patients in three main hospitals in Al-Najaf city. MRSA isolates were identified using PCR with primers specific for the mecA gene. PCR was used as the reference method, thus, the prevalence of MRSA in Najaf hospitals was 64 (47.4%) and the remaining 71 (52.6%) isolates were mecA-negative methicillin sensitive S. aureus (MSSA), and all MRSA isolates were tested for comparison using cefoxitin and oxacillin disc diffusion, oxacillin and methicillin HiComb E-test, oxacillin screen agar, BBLTM CHROMagarTM MRSA, HiCromeMeReSa agar. The findings of this study revealed that FOXDD had a high accuracy (97.8%) comparative to other phenotypic methods tested for detection of MRSA followed by OX (E-test), CHROMagar, HiCrome agar (97%), OXDD (96.3%). The OXSA (93.3%) and MET E-test (88.9%) had the lowest concordance with PCR results. Finally, FOXDD method may be preferred in this study and in other clinical laboratories because it is highly accuracy, easy to perform, low cost, and does not require special equipment.